Biophysical, Socioeconomic, and Geopolitical Vulnerabilities to Hydropower Development on the Nu River, China - Tullos, Disiree D. (The Resilience Alliance, 2015)
Rapid hydropower development is occurring in China’s Yunnan province in response to increasing clean energy demands, exposing potential vulnerabilities of the area’s ecosystems, communities, and geopolitical systems. Here, we present original data on the cultures, economics, hydro-politics, and environments of the Nu River basin, based on household surveys, analysis of geopolitical events, and hydrological, hydraulic, and landscape modeling. We identify sources of vulnerability and investigate relationships among biophysical, socioeconomic, and geopolitical elements that contribute to vulnerability. Our results illustrate the role of geographic isolation in intensifying vulnerability to hydropower development and how access to information, data uncertainty, and geopolitics influence the vulnerability of people and the environment. We emphasize specific needs for developing support mechanisms for social, ecological, and political groups that are vulnerable to hydropower development.